Ketahanan Pangan dan Gizi serta Mekanisme Bertahan pada Masyarakat Tradisional Suku Ciptagelar di Jawa Barat - Ali Khomsan; Hadi Riyadi; Sri Anna Marliyati (Jurnal Ilmu Pertanian Indonesia, 2013)
Culture plays an important role in food availability and consumption pattern, which then affects nutritional status and health. The objectives of the study were to analyze (1) socio-economic characteristics of household, (2) nutritional status of children, and (3) coping mechanism to support food access. The study was conducted in Ciptagelar Traditional Community, West Java from March-October 2013. Total sample was 65 households. The average income per capita per month was Rp285.753,00 and total expenditure was Rp393.590,00. The underweight prevalence among children was 12.5%, stunting 31.2%, and wasing 12.5%. Coping mechanisms to face income constraint were buying cheaper foods, reducing kinds of food consumed, and changing food priority.